2006
DOI: 10.1111/j.1742-4658.2006.05255.x
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐transfer capacity of catechin derivatives and influence on the cell cycle and apoptosis in HT29 cells

Abstract: Galloylated and nongalloylated catechin conjugates with cysteine derivatives have been synthesized and evaluated for their capacity to scavenge free radicals and to influence crucial functions (cell cycle, apoptosis) in HT29 colon carcinoma cells. We show that the nonphenolic part of the molecule modified the capacity of catechins to donate hydrogen atoms and to transfer electrons to free radicals. Nongalloylated derivatives did not significantly influence either the cell cycle or apoptosis. Among the galloyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 46 publications
3
36
0
1
Order By: Relevance
“…We have reported that conjugates of catechins with thiol-containing molecules such as cysteine and cysteamine share with other polyphenols their putatively beneficial antioxidant properties that are mainly attributed to the catechol or pyrogallol groups (Torres and Bobet, 2001;Lozano et al, 2006). We have also shown that the nonphenolic part of the molecule contributes significantly to the overall antioxidant effect.…”
Section: Discussionmentioning
confidence: 68%
“…We have reported that conjugates of catechins with thiol-containing molecules such as cysteine and cysteamine share with other polyphenols their putatively beneficial antioxidant properties that are mainly attributed to the catechol or pyrogallol groups (Torres and Bobet, 2001;Lozano et al, 2006). We have also shown that the nonphenolic part of the molecule contributes significantly to the overall antioxidant effect.…”
Section: Discussionmentioning
confidence: 68%
“…[13] By use of this radical, an intriguing observation that the electron-transfer capacity of catechin derivatives correlates well with cell-cycle-arrest activity and apoptosis-inducing activity in HT29 cells, was obtained. [14] Thus, HNTTMC was selected to evaluate the radicalscavenging property of hydroxylated stilbene-chroman hybrids (11 a-11 c) and their corresponding parent molecules resveratrol and PMC. When 11 b was added to the chloroform/methanol solution, the rapid disappearance of the visible absorption band of HNTTMC centered at 387 nm was accompanied by the appearance of a peak at 497 nm due to the formation of the corresponding anion HNTTM À (Figure 1), [13] indicating that the electron-transfer reaction from 11 b to HNTTMC took place.…”
mentioning
confidence: 99%
“…Conjugates were prepared by acidic depolymerisation of proanthocyanidins obtained from grape (Vitis Vinifera) pomace and from hazel (Hamamelis virginiana) bark, essentially as described inTorres and Bobet (2001) (5) andLozano et al (2006) (10). We aimed to generate bio-based antioxidants with modified physicochemical and biological properties.…”
mentioning
confidence: 99%